The Development of Higher Education and Academic Didactics - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2005)
The research problem, discussed in the article, is the influence of changes in higher education on the development of academic didactics. We argue that significant structural and functional changes had occurred in Lithuanian higher education during the last decade. These changes had inevitably influenced the nature of the academic work, including the didactics of higher education. However, despite a number of significant changes, due to the reasons indicated in the article a certain part of a wider society still consider that Lithuanian higher education had hardly changed at all. Besides a number of subjective factors, there also are objective ones which have contributed to such an image and which may evoke long-term negative consequences for further development of higher education in Lithuania.